PHILOSOPHICAL MESSAGES IN TUHAN MAHA ASYIK NOVEL FOR RELIGIOUS INCLUSIVITY - Ulya Ulya (Sekolah Tinggi Agama Islam Sadra, 2023)
In Indonesia, there has been a religious trend that emphasizes formality and exclusivity. As a result, conflicts among religious communities or groups within a particular religion are often unavoidable. This case certainly requires solutions, including intellectual solutions. This article explores the philosophical messages of the novel, Tuhan Maha Asyik (God is Fun), written by Sujiwo Tejo and MN. Kamba: contribution to their thought is related to religious attitudes; to get the pre-structure that influences their thought. This article is literature-based research with a hermeneutic approach. The main data source is the novel above, while data collection is done through documentation. The data analysis used is the Verstehen technique. The result shows that according to the novel, worshipping God and practicing His teachings should be based on love, doing good to fellow human beings, and not acting in the name of God to judge others; the ideas contribute to educating the mind and attitude of readers to develop inclusivity in religious life; the ideas are built by authors’ educational background, their life, and their religious tradition which ultimately influence their perspective and concept in understanding the issues of divinity and religiosity. This idea is one of the cultural capitals that needs to be internalized in Indonesian society, especially, to strengthen religious moderation and achieve harmonization in diverse lives.